ANALISIS DISTRIBUSI AIR DI KOTA BITUNG - Raymond Luntungan; Charles R. Ngangi; Paulus A. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
Water supply by PDAM Kota Bitung is still faced with various problems including the coverage of clean water services in Bitung city which has only reached 54.38 percent.  In this paper an evaluation of the technical aspects is carried out.  The number of house hold active customers in Bitung City is only 15,588 customers out of a total of 22,901 customers or only 68 percent of the total active customers.  The population of Bitung City is 212,409 people.  The population in the service area of PDAM Bitung is 214,108 people.               This type of research is descriptive quantitative to determine the needs of PDAM’s water in Bitung.  The type of data collected, consists of primary data and secondary data.  The domestic sector needs for household connections in 2028 will reach 172.77 litres per second while for public taps will be 10.27 litres per second.  The need for non-domestic sectors until 2028 will be 8.43 litres per second for education facilities, 21.22 litres per second for worship facilities, 0.92 litres per second for market facilities, 0.93 litres per second for hospital facilities, 0.48 litres per second  health center (puskesmas) facilities, 2.03 litres per second for hotel facilities, 0.2 litres per second for industrial area, and 8.85 litres per second for office and shops.  The Development of SPAM Piping Network of PDAM Bitung with zoning system consists of: Zone 1 Tandeki, Zone 2 Danowudu, Zone 3 Kadoodan, Zone 4 Kakenturan, Bitung Port Special Zone, Special Economic Zone (SEZ).Keywords: Water Distribution, Water Needs, Zoning